3D multicellular systems in disease modelling: From organoids to organ-on-chip - Goldrick, Caoimhe; Guri, Ina; Herrera-Oropeza, Gabriel; O’Brien-Gore, Charlotte; Roy, Errin; Wojtynska, Maja; Spagnoli, Francesca M. (Frontiers in Cell and Developmental Biology, 2023)
Cell-cell interactions underlay organ formation and function during homeostasis. Changes in communication between cells and with their surrounding microenvironment are a feature of numerous human diseases, including metabolic disease and neurological disorders. In the past decade, cross-disciplinary research has been conducted to engineer novel synthetic multicellular organ systems in 3D, including organoids, assembloids and organs-on-chip models. These model systems, composed of distinct cell types, satisfy the needs of better understanding complex biological interactions and mechanisms underpinning diseases. In this review, we discuss the emerging field of building multicellular systems and its application for modelling cellular interactions at play in diseases. We report recent experimental and computational approaches for capturing cell-cell interactions as well as progresses in bioengineering approaches for recapitulating these complexities ex vivo. Finally, we explore the value of developing such multicellular systems for modelling metabolic, gastrointestinal and neurological disorders as major examples of multisystemic diseases, we discuss the advantages and disadvantages of the different approaches and provide some recommendations for further advancing the field.